In a textbook of mine, there's a step which I can't get my head around.
B*E*X = A*(Y - E*X)
rearranges to
X = [A/(A+B)](Y/E)
I can't figure out how to do it. Could anyone walk me through it?
Thanks
p.s. Bonus points for knowing what the last equation is (A and B would normally be alpha and beta)
B*E*X = A*(Y - E*X)
rearranges to
X = [A/(A+B)](Y/E)
I can't figure out how to do it. Could anyone walk me through it?
Thanks
p.s. Bonus points for knowing what the last equation is (A and B would normally be alpha and beta)